Synthesis and Characterization of Ruthenium and Palladium Complexes of 2,2,6,6-Tetramethyl-3,5-heptanedione - Chen, Gaofang; Chang, Qiaowen; Chen, Xizhu; Ye, Qingsong; Hu, Changyi; Liu, Weiping (Asian Journal of Chemistry, 2012)
Ruthenium and palladium complexes of 2,2,6,6-tetramethyl-3,5-heptanedione were synthesized and characterized by elemental analyses, IR, 1H NMR, 13C NMR and UV. Thermal properties of these complexes were also studied by TG-DTA under air and nitrogen atmosphere.